Supercritical Fluid Extraction as a Successful Technique for Pesticides Estimation (Bangladesh Journal of Scientific and Industrial Research, 2010)
Recently Supercritical fluid extraction (SFE) has been focused as successful sample preparation step for pesticide multiresidue analysis due to its numerous advantages over classical solvent extractions (mainly rapidity, selectivity, low solvent volume requirement). However, developing SFE for pesticides is linked to numerous factors like pressure, temperature inside the cell, static time, flow rate and dynamic time (or fluid volume), volume of modifier added etc. Therefore, adequate knowledge is required for a new user to optimize the extraction performance for every new class of pesticides or new matrix to be analysed. Consequently, extraction parameters need to be carefully chosen. For instance, SFE of polar pesticides is enhanced by modifiers added to the matrix or the supercritical fluid. So this article discusses detail the principal strategies for efficient extractions of pesticides from several matrices. Key words: Supercritical fluid extraction (SFE); Pesticides; Pressure; Temperature; Matrix; Soxhlet extraction. DOI: 10.3329/bjsir.v45i1.5183 Bangladesh J. Sci. Ind. Res. 45(1), 47-56, 2010